2021
DOI: 10.1177/00016993211008517
|View full text |Cite
|
Sign up to set email alerts
|

Constructing fatherhood in the North and South: Paid parental leave, work and care in Iceland and Spain

Abstract: While Iceland and Spain historically belong to two different welfare regimes, both countries have enacted fathers’ quotas to their systems of paid parental leave. From the year 2000, Iceland has provided fathers with a three-month-long quota, and Spain introduced a 13-day fathers’ quota in 2007. Using survey data, the article applies structural equation modelling to learn of the interconnection between parents’ leave use, their working hours and fathers’ participation in care of their children. Fathers’ leave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 41 publications
0
13
0
3
Order By: Relevance
“…The study of doing fatherhood through the lens of alternative masculinities clearly requires more quantitative international comparisons. A promising start is the recent study by Arnalds and colleagues (2021) who compared father involvement in Iceland and Spain and found that leave use and reduced working hours increased care work participation. Future studies on the intersections of masculinities, fatherhood and mothering should also examine possible transformations of gender differences within care practices under different national conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The study of doing fatherhood through the lens of alternative masculinities clearly requires more quantitative international comparisons. A promising start is the recent study by Arnalds and colleagues (2021) who compared father involvement in Iceland and Spain and found that leave use and reduced working hours increased care work participation. Future studies on the intersections of masculinities, fatherhood and mothering should also examine possible transformations of gender differences within care practices under different national conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Si la mayoría de padres usan normalmente una parte significativa de los permisos parentales, eso se convierte en la norma masculina de paternidad y va modificando los roles de género (Arnalds et al, 2022). No obstante, es fundamental que los permisos estén bien remunerados para que los padres los usen (Ekberg et al, 2013;Castro-García y Pazos-Morán, 2016), y reducciones en la remuneración, ya sea en los techos máximos o las proporciones, reducen el uso de los permisos incluso en sociedades donde la igualdad de género está muy arraigada, como es el caso de los países nórdicos (Arnalds et al, 2022). Las partes transferibles, sean permisos individuales o familiares, son usados mayoritariamente por las madres (Castro-García y Pazos-Morán, 2016).…”
Section: Aprendizajes De La Evidencia Internacionalunclassified
“…Actualmente, Suecia solo tiene tres meses intransferibles de los hasta ocho meses que puede tener cada progenitor con parte de remuneración (el permiso parental bien remunerado y basado en los ingresos anteriores es de seis meses y medio para cada progenitor y se puede acceder a otro mes y medio transferible y escasamente remunerado a una cantidad fija, sumando un total de un año y cuatro meses) (íd.). Islandia, que equiparó entre madres y padres sus permisos parentales a partir del 2000, aunque manteniendo todavía un tercio la transferibilidad 2 , pudo aprender de sus socios nórdicos la relevancia de las «cuotas del papá» -los permisos no transferibles bien remunerados para los padres-, para que los usen, y directamente dio y sigue dando total flexibilidad para su uso (Arnalds et al, 2022;. La madre tiene obligación de coger dos semanas antes o después del parto (en Suecia es exclusivamente después del parto), pero el resto de semanas se pueden repartir como necesiten (Duvander y Löfgren, 2022;.…”
Section: Aprendizajes De La Evidencia Internacionalunclassified
“…The paradigm of Iceland has shown that when fathers made use of their parental leave following the introduction of the fathers' quotas, they were much more involved in parental care, with numerous benefits for the child's well‐being. This engagement was related to the duration of their paid leave 30 . In Iceland from 2000 to the present, parental leave has been divided between the first parent, the second parent and time to be used as the parents wished.…”
Section: Parental Leave‐sharing Among Parentsmentioning
confidence: 99%